Progresses of the badminton equipment relate to exercise: Some training aspects - Liang, Z.-Q.; Li, J.-S. (Journal of Sports Medicine and Therapy, 2018)
Background: With the development of sports science and badminton equipment, the roles of badminton shoes, such as to alter lower - extremity biomechanical parameters, prevent sports injuries and enhance performance, were confirmed by a mass of studies.